2019
DOI: 10.1371/journal.pone.0211265
|View full text |Cite
|
Sign up to set email alerts
|

Quality of routine facility data for monitoring priority maternal and newborn indicators in DHIS2: A case study from Gombe State, Nigeria

Abstract: IntroductionRoutine health information systems are critical for monitoring service delivery. District Heath Information System, version 2 (DHIS2) is an open source software platform used in more than 60 countries, on which global initiatives increasingly rely for such monitoring. We used facility-reported data in DHIS2 for Gombe State, north-eastern Nigeria, to present a case study of data quality to monitor priority maternal and neonatal health indicators.MethodsFor all health facilities in DHIS2 offering ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
151
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(169 citation statements)
references
References 44 publications
(55 reference statements)
6
151
2
Order By: Relevance
“…Over-reported routine HMIS data is a challenge in many countries in SSA [24,28]. Our results indicate a clear reduction in the variation of the mismatch, especially for OPD and IPD service areas from 2014 to 2017.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Over-reported routine HMIS data is a challenge in many countries in SSA [24,28]. Our results indicate a clear reduction in the variation of the mismatch, especially for OPD and IPD service areas from 2014 to 2017.…”
Section: Discussionmentioning
confidence: 70%
“…Since the error originates from the primary source it is di cult to correct it at later stages. A number of studies have reported similar ndings in other countries [11,12,24,26]. Our methodology detects that HF reports were manipulated before entering DHIS2.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations